Synthesis and applications on sensing technique of silver nanoparticle - Minakshi (Innovative Research Thoughts, 2018)
Medical diagnostics and medical gadgets, such as metal nanoparticles with diameters under 100 nm, have had a significant influence on customised healthcare during the last several decades. “Antimicrobial agents, biomedical device coatings, drug-delivery carriers, imaging probes, and diagnostic and optoelectronic platforms may all benefit from silver nanoparticles (AgNP) because of their unique physical and optical features and biochemical activity. In this study, we focused on the key synthesis methods for AgNPs, including physical, chemical, and biological synthesis processes, as well as the distinct physiochemical features of AgNPs. Molecular processes underpinning their plasmonic effects on mono- and bimetallic structures, as well as cytotoxicity to cells and microbes, are also discussed. Finally, we summarise the existing uses of AgNPs in nanoscience and nanomedicine and explore their prospects for the future in these fields.